2007
DOI: 10.1152/ajpendo.00445.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy worsens secondary hyperparathyroidism in mature rats during low-Ca diet

Abstract: Zhang Y, Lai W-P, Wu C-F, Favus MJ, Leung P-C, Wong M-S. Ovariectomy worsens secondary hyperparathyroidism in mature rats during low-Ca diet. Am J Physiol Endocrinol Metab 292: E723-E731, 2007. First published October 31, 2006; doi:10.1152/ajpendo.00445.2006.-Estrogen deficiency impairs intestinal Ca absorption and induces bone loss, but its effects on the vitamin D-endocrine system are unclear. In the present study, calciotropic hormones levels, renal vitamin D metabolism, 1,25-dihydroxyvitamin D3 [1,25(OH)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 46 publications
1
24
2
Order By: Relevance
“…Our results showed that the increase in serum PTH levels in mature female rats by WF treatment resulted in a significant reduction of urinary Ca excretion without any induction of serum 1,25(OH) 2 D 3 levels or bone resorption. The loss of association between serum PTH and serum 1,25(OH) 2 D 3 levels was also reported in our previous study that the significant increase in PTH levels in mature ovariectomised rats fed LCD did not result in any further increase in serum 1,25(OH) 2 D 3 levels (22) . However, it is of interest to find that the positive actions of WF treatment on Ca balance did not result in any increase in bone mass and bone properties in mature female rats in contrast to our previous reported study on aged female rats (22) .…”
Section: Discussionsupporting
confidence: 85%
“…Our results showed that the increase in serum PTH levels in mature female rats by WF treatment resulted in a significant reduction of urinary Ca excretion without any induction of serum 1,25(OH) 2 D 3 levels or bone resorption. The loss of association between serum PTH and serum 1,25(OH) 2 D 3 levels was also reported in our previous study that the significant increase in PTH levels in mature ovariectomised rats fed LCD did not result in any further increase in serum 1,25(OH) 2 D 3 levels (22) . However, it is of interest to find that the positive actions of WF treatment on Ca balance did not result in any increase in bone mass and bone properties in mature female rats in contrast to our previous reported study on aged female rats (22) .…”
Section: Discussionsupporting
confidence: 85%
“…32 Another possible factor involved in PTH regulation by estrogens could be calcitriol, but there is no clear evidence to support this hypothesis. Some experimental data suggest that estrogens do not influence calcitriol levels 14,33,34 ; meanwhile, others have shown that estrogens might modulate vitamin D receptor expression 34,35 and decrease serum calcitriol levels. 35,36 In our study, a significant dose-dependent decrease of serum calcitriol and PTH levels was observed with the use of estrogens ( Figures 1A and B and 3A); this decrease was strikingly higher in the case of calcitriol.…”
Section: Discussionmentioning
confidence: 99%
“…23 Fourth, gastric parietal cells appear to have a potent endocrine role in secreting estrogens. [24][25][26][27] Atrophy of the gastric mucosa, observed in patients infected with CagA-positive Helicobacter pylori, 28 reduces the number of gastric parietal cells and may decrease local production of estrogens. Estrogens produced in the stomach directly induce expression and production of ghrelin, 29,30 which appears to increase bone formation by osteoblasts.…”
Section: Introductionmentioning
confidence: 99%